2017
DOI: 10.1093/gji/ggx284
|View full text |Cite
|
Sign up to set email alerts
|

Extracting surface waves, hum and normal modes: time-scale phase-weighted stack and beyond

Abstract: Stacks of ambient noise correlations are routinely used to extract empirical Green's functions (EGFs) between station pairs. The time-frequency phase-weighted stack (tf-PWS) is a physically intuitive nonlinear denoising method that uses the phase coherence to improve EGF convergence when the performance of conventional linear averaging methods is not sufficient. The high computational cost of a continuous approach to the time-frequency transformation is currently a main limitation in ambient noise studies. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 85 publications
0
41
0
Order By: Relevance
“…To do so, instrument response Baker, 1979;Kasmarek & Robinson, 2004). We apply 1-bit normalization and autocorrelate 6-min segments (with 50% overlapping window) from a daily record and compute phase-weighted stacks (Ventosa et al, 2017). We apply 1-bit normalization and autocorrelate 6-min segments (with 50% overlapping window) from a daily record and compute phase-weighted stacks (Ventosa et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, instrument response Baker, 1979;Kasmarek & Robinson, 2004). We apply 1-bit normalization and autocorrelate 6-min segments (with 50% overlapping window) from a daily record and compute phase-weighted stacks (Ventosa et al, 2017). We apply 1-bit normalization and autocorrelate 6-min segments (with 50% overlapping window) from a daily record and compute phase-weighted stacks (Ventosa et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…To do so, instrument response removed data are demeaned, detrended, filtered between 0.01 and 8 Hz, and spectrally whitened. We apply 1-bit normalization and autocorrelate 6-min segments (with 50% overlapping window) from a daily record and compute phase-weighted stacks (Ventosa et al, 2017). Daily changes in seismic velocity (light gray lines) are found by grid search from −0.02 to 0.02 of dv/v that maximizes the correlation coefficient between the stretch-applied autocorrelograms and the reference autocorrelation record.…”
Section: Methodsmentioning
confidence: 99%
“…The seasonal variations of the secondary microseism during the whole 2014 are described through the study of surface-wave arrivals on the stacked CC traces for each month. According to the literature (Buffoni et al 2018;Kimman et al 2012;Schimmel et al 2017;Ventosa et al 2017), only the CC traces along Z component are shown from all the traces calculated along the Z, N and E components.…”
Section: Seasonal Changes Of the Secondary Microseism Investigated Bymentioning
confidence: 99%
“…Zeng and Thurber (2016) present a GPU implementation of the time-frequency phase-weighted stack (tf-PWS; Schimmel et al, 2011), which is up to 20 times faster than equivalent CPU implementations using the fast Fourier transform (FFT). Ventosa et al (2017) reduce computational cost of tf-PWS by introducing the timescale phase-weighted stack (ts-PWS) that uses the wavelet transform for the time-frequency representation, and propose unbiased phase coherence and two-stage ts-PWS to improve convergence speed and quality of the extracted signals. The unbiased phase coherence estimator contributes to increase noncoherent noise attenuation because it equals to 0 if the signals are totally incoherent.…”
Section: Introductionmentioning
confidence: 99%